2016
DOI: 10.1016/j.electacta.2016.04.090
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance, bifunctional oxygen electrode catalysed with palladium and nickel-iron hexacyanoferrate

Abstract: The development of air-breathing cathodes, which utilise atmospheric oxygen, enables the construction of lightweight, high energy density metal-air batteries and fuel cells. Air electrodes can be very lightweight and thin because the active material, oxygen, does not need to be stored inside the cell. However, air electrodes are restricted by poor reaction kinetics and low activity of many catalysts towards the oxygen evolution and reduction reactions. In addition, it is a challenge to maintain chemical and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Although Pd has been subject to extensive research with regards to fuel cell relevant electrocatalysis (e.g., its activity toward the hydrogen oxidation/evolution reaction (HOR/HER), [7][8][9] its robustness against poisoning in PEMFC anodes, 10 or its activity toward the electrochemical oxidation of small organic molecules 11 ), its activity toward the ORR has often been examined as a co-material to Pt [12][13][14] or other metals (e.g., as alloy component or core material for core-shell particles), 15 either focusing on the reduction of the required Pt amount or on the enhancement of catalyst activity for the ORR. Comprehensive reviews were given by Antolini and Shao.…”
mentioning
confidence: 99%
“…Although Pd has been subject to extensive research with regards to fuel cell relevant electrocatalysis (e.g., its activity toward the hydrogen oxidation/evolution reaction (HOR/HER), [7][8][9] its robustness against poisoning in PEMFC anodes, 10 or its activity toward the electrochemical oxidation of small organic molecules 11 ), its activity toward the ORR has often been examined as a co-material to Pt [12][13][14] or other metals (e.g., as alloy component or core material for core-shell particles), 15 either focusing on the reduction of the required Pt amount or on the enhancement of catalyst activity for the ORR. Comprehensive reviews were given by Antolini and Shao.…”
mentioning
confidence: 99%
“…Graphene contains a single-atom thick and two-dimensional structure, and it is a superior material to enhance the interaction and dispersion of metal [20]. Therefore, graphene could improve the redox reaction [18,21,22], which has been previously demonstrated by the study of Pd catalysts supported on other types of carbon materials [23][24][25][26][27]. Fast ORR can be triggered effectively with precious metals [14][15][16][17], since they form coordination bonds and participate in ORR through their vacant d orbits [14,18].…”
Section: Introductionmentioning
confidence: 95%
“…GDC modified with nitrogen doped graphene at carbon nanotube electrodes have been reported as effective for the generation of 25 mg dm −3 of H 2 O 2 at an applied potential of − 0.5 V vs. standard calomel electrode (SCE) 32 . The study to improve GDC modified with Fe (II) catalyst showed about 99% decolorization of methylene blue in 250 min at − 1.0 V vs. Hg/HgSO 4 33 . Nitrogen functionalised carbon nanotube cathodes was observed to be useful for complete degradation of methyl orange at − 0.85 V in 60 min 29 .…”
Section: Introductionmentioning
confidence: 97%